Effect of dynamic compaction by multi-point tamping on the densification of sandy soil. (November 2022) - Yao, Zhanyong; Zhou, Chong; Lin, Qiqi; Yao, Kai; Satchithananthan, Umashankaran; Hou Lee, Fook; Minh Tang, Anh; Jiang, Hongguang; Pan, Yutao; Wang, Songtao
Abstract: This paper examines the effect of dynamic compaction by multi-point tamping on the densification of sandy soil between adjacent impact points. First, by using a three-dimensional finite element analysis, tamping was modelled using drop weight with prescribed impact velocity. The numerical model was then validated with centrifuge model test results for single-point tamping. Afterward the numerical model was used to predict the soil densification by multi-point tamping. The numerical results led to an empirical method for estimating the effect of compaction on sandy soil at any location within the grid, which accounts for the effect of depth below ground surface, standoff distance, and tamping sequence. A parametric study was subsequently performed to investigate the effect of these parameters. Finally, a design approach was proposed for dynamic compaction projects. The performance of this approach was assessed by using data collected from three field cases.